2021
DOI: 10.1038/s41419-020-03342-8
|View full text |Cite
|
Sign up to set email alerts
|

Homotypic CARD-CARD interaction is critical for the activation of NLRP1 inflammasome

Abstract: Cytosolic inflammasomes are supramolecular complexes that are formed in response to intracellular pathogens and danger signals. However, as to date, the detailed description of a homotypic caspase recruitment domain (CARD) interaction between NLRP1 and ASC has not been presented. We found the CARD–CARD interaction between purified NLRP1CARD and ASCCARD experimentally and the filamentous supramolecular complex formation in an in vitro proteins solution. Moreover, we determined a high-resolution crystal structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 58 publications
6
16
0
Order By: Relevance
“…S2c and d). Our results are consistent with previous reports [20][21][22][23] that ASC is an indispensable, dispensable and independent adaptor in NLRP1, mNLRP1b and CARD8 inflammasome assembly, respectively.…”
Section: Distinct Asc Preference Is Dependent On Card But Not Upa Dom...supporting
confidence: 94%
See 2 more Smart Citations
“…S2c and d). Our results are consistent with previous reports [20][21][22][23] that ASC is an indispensable, dispensable and independent adaptor in NLRP1, mNLRP1b and CARD8 inflammasome assembly, respectively.…”
Section: Distinct Asc Preference Is Dependent On Card But Not Upa Dom...supporting
confidence: 94%
“…More importantly, we also found that multiple molecular surfaces were involved in the interaction of NLRP1 UPA-CARD and Caspase-1 CARD to transduce downstream signals, which is consistent with the Mosaic model that DD superfamily members co-assemble into archetypical supramolecular platform by three conserved interaction types 21 (Fig. 5e and S3a-d).…”
Section: Structure Basis For Card Domain-mediated Asc Preferencesupporting
confidence: 88%
See 1 more Smart Citation
“…The ASC dependence varies for each inflammasome, while pro-Casp-1 activation in NLRP3 and AIM2 inflammasomes requires ASC, the presence of ASC enhances pro-inflammatory signaling in CARD containing sensors, such as NLRP1 and NLRC4 [ 14 , 15 ]. Recently, structural studies showed direct interaction between NLRP1 CARD and ASC CARD and between NLRC4 CARD and ASC CARD [ 16 , 24 ]. As inflammatory responses depend on the activation of more than one inflammasome in several diseases [ 25 27 ], any drug that can inhibit numerous inflammasome complexes simultaneously would be of significant interest.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammasomes are made up of a sensor protein such as NLR containing protein that detects the danger signals and recruits adaptors such as ASC. ASC ultimately incorporates effector proteins into the assembly for example caspase-1 via homotypic death domain interactions which results in higher-order assembly of inflammasomes yielding activated caspases [4][5][6]. The NLR/ALR-containing inflammasome are often termed as canonical inflammasomes, for example, NLRP3 inflammasome.…”
Section: Introductionmentioning
confidence: 99%